Phytochemical Profile and Antioxidant Activity of Phenolic and Flavonoid Compounds in Methanol Extracts of the Fruit and Leaves of Scaevola taccada (Geartn.) Roxb - Hasbi Assidiqi Nasution; Indriaty Indriaty; Marjanah Marjanah (Biology, Medicine, & Natural Product Chemistry, 2026)
The mangrove plant Scaevola taccada (Gaertn.) Roxb is known to have potential as a source of natural bioactive compounds that act as antioxidants. The presence of antioxidant compounds can control ROS (Reactive Oxygen Species) and RNS (Reactive Nitrogen Species), which trigger oxidative stress. The purpose of this study is to assess the antioxidant activity and total phenolic and flavonoid content of methanol extracts from the fruits and leaves of Scaevola taccada originating from the coastal area of Sikara-kara Village, Mandailing Natal Regency. This study is an experimental study conducted in vitro in a laboratory. The extraction process was performed using the maceration method with 80% methanol as the solvent. Total phenolic compounds were measured using the Folin-Ciocalteu method with gallic acid as the standard, while total flavonoids were measured using the aluminum chloride method with quercetin as the standard. Antioxidant activity was measured using the DPPH method, with the results expressed as IC50 values. The findings indicated that the leaf extract possessed elevated concentrations of phenolics and flavonoids relative to the fruit extract, with a total phenolic content of 68.896 mg GAE/g extract and a total flavonoid content of 103.612 mg QE/g extract. The fruit extract exhibited a total phenolic value of 43.916 mg GAE/g extract and a total flavonoid value of 11.287 mg QE/g extract. Leaf extract exhibits superior antioxidant activity, evidenced by an IC50 value of 52.832 ppm, in contrast to 342.386 ppm for the fruit extract. This study shows that the leaves of Scaevola taccada have greater potential as a source of antioxidants than the fruit, thereby opening up opportunities for their use as raw materials in the production of herbal medicines.